A Review of Metal‐ and Metal‐Oxide‐Based Heterogeneous Catalysts for Electroreduction of Carbon Dioxide. (7th May 2018) - Liu, Guanyu; Tran‐Phu, Thanh; Chen, Hongjun; Tricoli, Antonio
Abstract: Capping and, eventually, reducing the atmospheric levels of greenhouse gases such as CO2 is an urgent priority, and a focus of multidisciplinary efforts. Among other techniques, advanced technologies for CO2 capture and conversion are highly desirable to limit CO2 emissions. Electrochemical reduction of CO2, using off‐peak renewable electricity, to value‐added chemicals and fuels has attracted extensive research interest. A main effort is directed toward the development of efficient, selective, and robust electrocatalysts to promote CO2 reduction, due to its sluggish reaction kinetics. Here, recent investigations and achievements in the design of metal‐ and metal‐oxide‐based heterogeneous catalysts are reviewed in terms of catalytic activity, selectivity, stability, and mechanism. A classification of heterogeneous CO2 catalysts is presented based on the main products of electrochemical reduction of CO2, including HCOOH, CO, C2 H4, CH3 OH, and C3 H8 O. The key catalysts' properties favoring the production of specific chemical products from the CO2 reduction reaction are critically discussed. The challenges for achieving superior CO2 reduction electrocatalysts are discussed providing future research directions for their design and development. Abstract : A classification of heterogeneous CO2 catalysts is presented based on the main products of the electrochemical reduction of CO2, including HCOOH, CO, C2 H4, CH3 OH, and C3 H8 O, in terms of catalytic activity, selectivity, stability, and mechanism. The key catalysts' properties favoring the production of specific chemical products from the CO2 reduction reaction are critically discussed.